2020
DOI: 10.36130/ctd.03.2020.04
|View full text |Cite
|
Sign up to set email alerts
|

Short Implants Versus Bone Augmentation and Longer Implants in Atrophic Maxillae. Five Year Post Loading Results of a Randomised Controlled Trial

Abstract: Randomised controlled trial PURPOSE. To evaluate whether short (5 to 8.5 mm) dental implants could be a suitable alternative to longer (at least 11.5 mm long) implants for supporting dental prostheses placed in atrophic fully edentulous maxillae augmented with autogenous bone. MATERIALS AND METHODS.Twenty-eight patients with fully edentulous atrophic maxillae having 5 to 9 mm of residual crestal bone height at least 5 mm thick, as measured on CT scans, were randomised into two groups, either to receive four to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 7 publications
3
29
0
Order By: Relevance
“…It is difficult to compare the results of the present trial with those of similar studies, as these could not be found in the published literature. That being said, our results do show interesting similarities to those of other RCTs investigating vertical atrophy cases, comparing 4-to 6.6-mm short implants versus augmentation procedures to place 10 mm or longer implants [9][10][11][12][13][14] . Such results, obtained in vertically atrophic mandibles, were also summarised in a recent systematic review 15 ; together they suggest that augmentation procedures to create new supporting bone are more technically demanding than placing narrow-diameter or short implants, and are generally associated with higher post-operative morbidity, more complications, longer treatment periods and an increased number of surgeries.…”
Section: Discussionsupporting
confidence: 79%
“…It is difficult to compare the results of the present trial with those of similar studies, as these could not be found in the published literature. That being said, our results do show interesting similarities to those of other RCTs investigating vertical atrophy cases, comparing 4-to 6.6-mm short implants versus augmentation procedures to place 10 mm or longer implants [9][10][11][12][13][14] . Such results, obtained in vertically atrophic mandibles, were also summarised in a recent systematic review 15 ; together they suggest that augmentation procedures to create new supporting bone are more technically demanding than placing narrow-diameter or short implants, and are generally associated with higher post-operative morbidity, more complications, longer treatment periods and an increased number of surgeries.…”
Section: Discussionsupporting
confidence: 79%
“…It is difficult to compare the results of the present trial with those from similar trials, as these could not be found in the published literature. That being said, our results do show interesting similarities to those of other RCTs investigating vertical atrophy cases, comparing 4-to 6.6-mm short implants versus augmentation procedures to place 10 mm or longer implants [7][8][9][10][11][12] . Such results, obtained in vertically atrophic mandibles, were also summarised in a recent systematic review 13 ; together they suggest that augmentation procedures to create new supporting bone are more technically demanding than placing small-diameter or short implants, and are generally associated with higher post-operative morbidity, complications, longer treatment periods and an increased number of surgeries.…”
Section: Discussionsupporting
confidence: 79%
“…Short dental implants (4 to 8 mm long) 1 have been reported as an appealing and less invasive alternative to bone augmentation procedures for placing longer implants, with both groups displaying similar results up to 11 years after loading [2][3][4][5][6][7][8][9][10][11] . One of the issues often debated is whether it is better or not to join two or more short implants under the same prosthesis to decrease the potential risks of failures or mechanical complications such as screw loosening.…”
Section: Introductionmentioning
confidence: 99%